Low dose effects of a Withania somnifera extract on altered marble burying behavior in stressed mice - Dey A.; Chatterjee S.S.; Kumar V. (My University, 2025)
Aim: Withania somnifera root (WSR) extracts are often used in traditionally known Indian systems of medicine for prevention and cure of psychosomatic disorders. The reported experiment was designed to test whether low daily oral doses of such extracts are also effective in suppressing marble burying behavior in stressed mice or not. Materials and Methods: Groups of mice treated with 10, 20, or 40 mg/kg daily oral doses of WSR were subjected to a foot shock stress-induced hyperthermia test on the 1st, 5th, 7th, and 10th day of the experiment. On the 11th and 12th treatment days, they were subjected to marble burying tests. Stress response suppressing effects of low dose WSR were estimated by its effects on body weight and basal core temperature of animals during the course of the experiment. Results: Alterations in bodyweight and basal core temperature triggered by repeated exposures to foot shock stress were absent even in the 10 mg/kg/day WSR treated group, whereas the effectiveness of the extract in foot shock stress-induced hyperthermia and marble burying tests increased with its increasing daily dose. Conclusion: Marble burying test in stressed mice is well suited for identifying bioactive constituents of W. somnifera like medicinal plants with adaptogenic, anxiolytic and antidepressant activities, or for quantifying pharmacological interactions between them. © SAGEYA.